Qualidade de vida relacionada à saúde bucal de usuários de prótese total e prótese parcial removível - Mesko, Mauro Elias (2012)
Longevity increase is not directly related to quality of life. In Dentistry, it became in evidence by the fact that almost twenty-five percent of the population between 65 and 74 year-old presents a completely edentulous arch. As the elderly have a higher probability of being affected by chronic oral problems they tend to demand complex treatments. The aim of this survey was to: (i) evaluate the relationship between the Oral Health Impact Profile (OHIP-EDENT) and Geriatric Oral Health Assessment Index (GOHAI) questionnaires to assess the oral health quality of life in denture wearers, (ii) evaluate the associated factors to impairment in the oral health quality of life in elderly wearing removable dentures using the OHIP- EDENT and GOHAI. Evaluation of the oral health quality of life in complete denture and removable partial denture wearers was performed according to the World Health Organization criteria. The survey consisted of applying GOHAI and OHIP-EDENT questionnaires and a clinical examination. Questions about socioeconomic conditions were applied aiming to determine which factors have an influence in oral health related quality of life. The hypotheses tested were (1) different questionnaires would provide similar results when assessing oral health quality of life in totally or partially edentulous patients wearing prosthesis; (2) age, socioeconomic profile, type and location of the prosthesis and their stability and retention would not be associated to the oral health quality of life. The results showed that the questionnaires are different tools when both the total and adjusted values were compared. The exception was for Kennedy Class I and II removable partial dentures wearers. Mandibular complete dentures caused a higher impact in individuals quality of life, except for the removable partial denture wearers. For the patients aged 60 years old or more the questionnaires showed themselves quite different. Among the subscales, the only statistically difference was found in functional limitation and the domains food catching was the one that showed difference in the removable partial denture wearers group. Using the same questionnaires the variables age, familiar income, type of prosthesis, stability and retention of the prosthesis were evaluated. Factors associated to the 14 impact in OHRQoL were familiar income, stability and retention of the prostheses. Therefore, OHIP-EDENT and GOHAI are different tools, especially when used with individuals older than 60 years old, poor denture quality was associated to the impact in quality of life while income had influence on the results